Where energy poverty limits not only lights but lives: Discussions in rural Pakistan on the importance of clean energy to women - Khalid, Sidra; Hafeez, Mohsin (CGIAR, 2024)
Focus group discussions conducted by IWMI reveal how clean energy positively impacts women in Pakistan